2007
DOI: 10.1002/jrs.1679
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of plasma contribution in femtosecond degenerate four‐wave mixing (fs‐DFWM) at high intensity

Abstract: Femtosecond Degenerate Four Wave Mixing (fs-DFWM) experiments in CO 2 exhibit a strong background due to plasma produced at high intensity (≥20 TW/cm 2 ), when significant molecular alignment is likely to arise. This perturbing phenomenon renders the measurements of alignment very difficult. It is shown that the plasma contribution can be avoided by employing perpendicular polarizations for the two pump pulses. The effect is explained on the basis of the different diffraction angles between signals produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The background has repeatedly been detected experimentally. 8,[12][13][14][15][16][17][18][19][20] To describe it, a formula…”
Section: Perturbative Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The background has repeatedly been detected experimentally. 8,[12][13][14][15][16][17][18][19][20] To describe it, a formula…”
Section: Perturbative Approachmentioning
confidence: 99%
“…[9][10][11] To improve the signal-to-noise, rather strong laser pulses are frequently used, so that the standard ͑weak field͒ theory is no longer applicable. Furthermore, strong pulses cause several interesting features in femtosecond DFWM signals, 8,[12][13][14][15][16][17][18][19][20] which are not entirely understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of higher electronic surfaces in H 2 and the control of the shapes of vibrational wave packets were discussed. Femtosecond degenerate fourwave mixing (DFWM) experiments in CO 2 at high intensity were performed by Rouzée et al 71 A strong background due to plasma formation was observed in these samples. The authors showed that the plasma contribution can be avoided by employing perpendicular polarizations for the two pump pulses.…”
Section: Other Nonlinear Techniquesmentioning
confidence: 99%
“…[11] CARS spectroscopy has been performed via single-beam [12,13] coherently engineered by spatial light modulation, optimal control [14] and tunable supercontinuum source from photonic-crystal fibers. [15,16] Recently, CARS is also used to study molecules in background plasmas [17] and terahertz regime, [18] simultaneous detection of multi-species gas [19] , determination of temperature [20] and collision induced dephasing and rotational energy transfer. [21] Good reviews on the fundamentals, developments and applications of CARS technique were given by Kiefer [22] and Zheltikov.…”
Section: Introductionmentioning
confidence: 99%